2002
DOI: 10.5194/angeo-20-203-2002
|View full text |Cite
|
Sign up to set email alerts
|

Doppler temperatures from O(<sup>1</sup>D) airglow in the daytime thermosphere as observed by the Wind Imaging Interferometer (WINDII) on the UARS satellite

Abstract: Abstract. From 1992 to 1997, the WINDII interferometer on board the UARS satellite acquired a large set of thermospheric data from the O( 1 D) and O( 1 S) airglows. We report here for the first time on daytime O( 1 D) Doppler temperatures obtained with version 5.11 of the WINDII data processing software. Using a statistical analysis of the temperatures independently measured by the two WINDII fields of view, we estimate that the temperature variations larger than 40 K can be considered as geophysical. Comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Physical approaches consist in feeding the models with observations. These observations can for example be the UV airglow (Nicholas et al 2000), the thermospheric temperature (Lathuillère et al 2002), or ionospheric parameters such as the Total Electron Content (TEC) (Lilensten and Blelly 2002).…”
Section: Satellite Drag: a Thermospheric Processmentioning
confidence: 99%
“…Physical approaches consist in feeding the models with observations. These observations can for example be the UV airglow (Nicholas et al 2000), the thermospheric temperature (Lathuillère et al 2002), or ionospheric parameters such as the Total Electron Content (TEC) (Lilensten and Blelly 2002).…”
Section: Satellite Drag: a Thermospheric Processmentioning
confidence: 99%
“…An improved method to derive vertical profiles of temperature and wind was developed in which temperature and wind parameters were discretized in the spatial domain. A linearly constrained least squares algorithm was then applied with results presented in [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Between 1992 and 1997, the WINDII interferometer on board the UARS satellite acquired a large set of thermosphere data from the O( 1 S) and O( 1 D) airglow. Doppler temperature profiles from 180 to 260 km altitude were retrieved from the O( 1 D) data and compared with modeled temperatures [ Lathuillère et al , 2002]. Restricting their analysis to 33 quiet magnetic days, the authors have shown that temperatures predicted by the two semiempirical models DTM94 [ Berger et al , 1998] and MSIS‐90 [ Hedin , 1991] were in excellent agreement with the observed latitudinal/local time and solar activity variations of the WINDII temperatures.…”
Section: Introductionmentioning
confidence: 99%